Wspomaganie komunikacji osób z niepełnosprawnością intelektualną - przegląd wybranych metod ze wskazówkami w tle = Supporting communication of people with intellectual disabilities - overview of selected methods with background guidance - Przybysz-Zaremba, Małgorzata (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
Communication is undoubtedly an important area of life and social functioning of people with intellectual disabilities. The text reviews selected alternative and supportive methods/techniques for this group of people,deeper forms of disabilities included). In the final part of the text we have placed a set of indications specifying the conditions that should be met when using these methods/techniques.
Keywords: komunikacja; niepełnosprawność intelektualna; metody alternatywne i wspomagające; communication; intellectual disability; alternative and supportive methods/techniques